GOVERNMENTAL AND ORGANISATIONAL FACTORS AS PREDICTORS OF OCCUPATIONAL HEALTH AND SAFETY OF FEMALE WORKERS IN INDUSTRIES IN LAGOS STATE, NIGERIA (2011)
The protection of workers generally against health and safety hazards at work environments has been emphasised adequately in International Labour Organisation Conventions and Recommendation. Nigeria, being a signatory to these conventions and recommendations, must ensure strict compliance to the protection of the health and safety of the working class, particularly the female workers. Previous studies have focused more generally on safety standards and conditions at work with little attention on governmental and organisational factors that guarantee maximum provision of occupational health and safety of female workers. This study, therefore, examined the extent to which governmental (legislations, enforcements, monitorings, sanctions, incentives, social policy measures) and organisational factors (management attitudes/dispositions, organisational welfare policies, physical work environment and training and re-training) predict occupational health and safety of female workers in industries in Lagos state, Nigeria. The study adopted the survey research design. Multi stage sampling procedure was used to select 1084 junior female factory workers from 14 food and beverages industries. Data were collected using Governmental Factors Questionnaire (r = 0.79), Organisational Factors Questionnaire (r = 0.93) and Occupational Health and Safety Scale (r = 0.85). These were complemented with seven sessions of Focus Group Discussion (FGD) with the female factory workers. Four research questions were answered and two hypotheses tested at 0.05 level of significance. Data were analysed using percentages, t- test and Multiple regression and content analysis. Governmental and organisational factors jointly predicted occupational health and safety of female workers and contributed 24.47% to the variance of independent variable. There were significant contributions of independent variables (Governmental factors) (F(3,1080)=86.12, p<0.05) and (Organisational factors) (F(3,1080)=62.42, p<0.05) on occupational health and safety of female workers. Five components of governmental factors made significant relative contributions in the following order: legislations (?=.41; p<0.05), monitoring (?=.37; p < 0.05); enforcements (?=.24; p< 0.05); social policy measures (?=.17; p< 0.05), sanctions (?=.13; p< 0.05). Incentives had no significant relative contribution. Each of the organisational factors predicted occupational health and safety of female workers as follows: management attitudes/dispositions (?=.36; p< 0.05), organisational welfare policies (?=.30; p< 0.05) and training and re-training (?=.22; p< 0.05) while physical work environment had negative contribution. However, there was no significant difference in the health and safety needs of single and married junior female factory workers. The FGD sessions revealed that many of the junior female factory workers believed that paying particular attention to certain governmental and organisational factors enhanced their occupational health and safety in the work place. Legislation, enforcement, monitoring, sanctions, social policy measures, management attitudes/dispositions, organisation welfare policies, physical work environment and training and re-training were critical factors in ensuring female workers occupational health and safety. Therefore, these governmental and organisational factors should be addressed by all employers of labour both in the public and organised private sectors in guaranteeing the protection of female workers against occupational hazards that could threaten their health and safety at work environments.